Analysis of the Increase in Payload Capacity of Airbus A320 Aircraft at Radin Inten II International Airport Lampung Using an Improved Climb Approach - Lukito, Indro; Budiono, Cyrilus Sukaca; Prakoso, Agung; Poerwanto, Eko; Mardwianta, Benedictus (Institut Teknologi Dirgantara Adisutjipto, 2025)
This study aims to analyze the increase in the payload capacity of the Airbus A320 at Radin Inten II International Airport Lampung using the Improve Climb approach. The Improve Climb approach focuses on optimizing the aircraft's climb path to enhance efficiency and payload capacity, particularly in airport conditions with high elevation and unfavorable weather. This study includes an analysis of the performance data of the Airbus A320. In addition, flight simulations were conducted taking into account factors such as wind speed, air temperature, and engine power. The results of this analysis are expected to provide recommendations regarding the optimization of flight schedules, passenger capacity, and improvements in operational efficiency at the airport. The results of the study indicate that by applying the Improve Climb approach, the aircraft's payload capacity can be increased by up to 3% without compromising safety. This opens up opportunities to increase the number of passengers.